Displaying Bone Scans in Color - Pérez-Meza, M.; Jaramillo-Núñez, A.; Sánchez-Rinza, B. E. (Revista Mexicana de Ingenieria Biomedica, 2018)
The use of software based on a quantitative method for detecting skeletal metastasis in bone scans is presented. Forty-three bone scans of patients with prostate cancer were previously analyzed visually by three specialists and their diagnosis were taken as a reference. Later, these scans were analyzed by segmenting them into four regions: skull, shoulders, chest, and pelvis. The segmentation was made to obtain intervals of gray levels for each of the regions using a statistical process. These values were found by calculating the mean and standard deviation of four samples containing each forty-three regions. Using these intervals, seven colors were assigned to each region. By means of the colors it is possible to differentiate healthy and infiltrated cases in each region, which may facilitate the diagnosis. Examples of results in each region are shown.